The Perspective of the Community in the Medan Kota Sub-District on the Open and Closed Proportional Representation Electoral System - Lubis, Mhd Ansor (Faculty of Law, Universitas Pekalongan, 2024)
Open and closed proportional electoral systems have a significant impact on voter participation in 2024, especially in the Medan Kota area. This is in line with the level of public understanding of the electoral system that has just been decided by the Constitutional Court No. 114/PUU-XX/2022. This study endeavors to ascertain the extent of the voting public's comprehension regarding the proportional electoral system. This research method uses normative juridical and is presented in a descriptive analysis by providing an overview of the object under study and linking it to legal literature both primary Additionally, this study relies on secondary data. The findings revealed that public participation in the proportional election system within Medan city remained at a relatively low level, specifically at 46.5%. Of the 30.8% early voters, those aged 20 to 60 years increased from 37 to 54%. This is due to the voters' lack of understanding of the proportional system, both directly and indirectly.